Acute effects of caffeine on intraocular pressure - Riaz, Irum; Muhammad Fayaz; Fatima Zahid; Sadia Noureen; Hakim Anjum Nadeem; Mehronisa (Journal of the Pakistan Medical Association, 2025)
Objective: To examine the acute effects of caffeine on the intraocular pressure among healthy young individuals. Method: The quasi-experimental study was conducted from January to May 2023 at the Superior University, Lahore, Pakistan, while data was collected from Al-Khair Trust Eye Hospital, Lahore. The sample comprised subjects aged 18-27 years who had healthy eyes and were non-habitual consumers of coffee. Blood pressure and intraocular pressure were measured at baseline and then again at 30, 60 and 90 minutes after coffee ingestion. Individuals were given freshly produced instant coffee with caffeine. After an interval of two days, the same group was given instant decaffeinated coffee. Data was analysed using SPSS 25. Results: Of the 73 subjects, 46(63%) were males and 27(37%) were females. The overall mean age was 22.52±2.08 years (range: 19-27 years). Caffeine consumption raised intraocular pressure (p<0.001) and blood pressure (p=0.007) significantly compared to the baseline. Group B show no significant change (p>0.05). Conclusion: There was a significant increase in intraocular pressure and blood pressure after coffee ingestion in the caffeinated group, while there was no significant change in the decaffeinated group. Key Words: Caffeine, Intraocular pressure, Glaucoma.